Study on the detection of tetracycline by electrochemical sensors modified with nanomaterials - WANG Chenyu; LI Xiaoran; QUAN Ke; LIU Miao; WANG Jianhui; CHEN Qijie; ZHANG Bo (Shipin yu jixie)
Tetracycline (TC) is a typical broad-spectrum antibiotic with extensive applications in fields such as food and medicine. However, its improper use can pose a threat to human health and environmental safety. Therefore, detecting the residue of tetracycline is very important. In recent years, electrochemical sensors modified with nanomaterials have been successfully applied for the detection of tetracycline residues in food and environmental samples due to their high sensitivity and fast response. This review compares the electrochemical sensors modified with different nanomaterials for tetracycline detection, aiming to provide a reference for trace analysis of tetracycline and the development of more efficient detection technology. At the same time, this review also summarizes the existing problems of tetracycline-detecting electrochemical sensors and the prospects for their development.